2020
DOI: 10.1101/2020.04.28.20082552
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can Nebulised Heparin Reduce Time to Extubation in SARS-CoV-2 (CHARTER Study) – Protocol

Abstract: Introduction: COVID-19 is associated with the development of ARDS displaying the typical features of diffuse alveolar damage with extensive pulmonary coagulation activation resulting in fibrin deposition in the microvasculature and formation of hyaline membranes in the air sacs. The anti-coagulant actions of nebulised heparin limit fibrin deposition and progression of lung injury. Serendipitously, unfractionated heparin also inactivates the SARS-CoV-2 virus and prevents its entry into mammalian cells. Nebulisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…1B ) The observed inhibition may be due to direct competition of the exogenous heparin for host cell surface GAGs and/or for the ACE2 receptor and demonstrates that addition of exogenous heparin can disrupt the interaction of the virus with the cell. It is noteworthy that the heparin concentrations used cover both prophylactic and therapeutic heparin nebulisation protocols, 38 highlighting that this in vitro regime correlates with heparin use clinically, which is not the case for some of the other drugs tested thus far against COVID, e.g. ivermectin.…”
Section: Resultsmentioning
confidence: 99%
“…1B ) The observed inhibition may be due to direct competition of the exogenous heparin for host cell surface GAGs and/or for the ACE2 receptor and demonstrates that addition of exogenous heparin can disrupt the interaction of the virus with the cell. It is noteworthy that the heparin concentrations used cover both prophylactic and therapeutic heparin nebulisation protocols, 38 highlighting that this in vitro regime correlates with heparin use clinically, which is not the case for some of the other drugs tested thus far against COVID, e.g. ivermectin.…”
Section: Resultsmentioning
confidence: 99%
“…Additional studies report that soluble unfractionated heparin and its derivatives inhibit SARS-CoV-2 host cell entry in vitro (Partridge et al, 2020;Tandon et al, 2020). Nebulized Heparin is currently being evaluated in COVID-19 patients (Dixon et al, 2020) and a separate clinical study demonstrates the association between heparin and lower mortality in COVID-19 patients (Ayerbe et al, 2020). With additional randomized controlled trials in various therapeutic regimes (Ayerbe et al, 2020), HP may be an excellent candidate to be repurposed as prophylactic COVID-19 therapeutic.…”
Section: Discussionmentioning
confidence: 99%
“… 54 In addition, post-mortem studies and lung biopsies of patients with SARS-CoV-2 infection and ARDS have shown hyaline membranes in the alveolar spaces and extensive pulmonary microvascular thrombi, suggesting a potential role for nebulised heparin in the treatment of COVID-19 pneumonia, which is currently under clinical investigation. 28 , 29 , 55 , 56 , 57 , 58 …”
Section: Discussionmentioning
confidence: 99%